A Highly Aggressive Choriocarcinoma of Tubo-Ovarian Mass: A Rare Case Report - Bano, Shahnaz; Singh, Bhanu Pratap; Hirani, Nilopher (Annals of Pathology and Laboratory Medicine, 2024)
Background: Choriocarcinoma is a rare and highly aggressive tumor of trophoblastic origin. The most common location of choriocarcinoma is intrauterine; however, rare sites include the fallopian tube, ovary, and elsewhere in the abdomen and pelvis. Case details: A 46-year-old woman, with a gestational history of G5P5Sb5, presented to the gynecology OPD with complaints of abdominal pain for four to six (4–6) months and a history of irregular menstrual periods. CECT chest and abdomen revealed a large left adnexal mass, moderate ascites, and pleural effusion. Serial beta-HCG levels were elevated. Specimens of the uterus, right salpingo-oophorectomy, and left adnexal mass were received for histopathological examination. On gross examination, there was a grayish, irregular left adnexal tissue mass measuring 20 × 14 × 9.0 cm. On cut section, multiple necrotic, hemorrhagic, and cystic areas were noted. No gross abnormalities were seen in the uterus, right fallopian tube, and right ovary. Multiple sections studied from the en masse tissue showed sheets of atypical syncytiotrophoblast and cytotrophoblast with two to three (2–3) mitotic figures per ten (10) high-power fields. The tumor showed an infiltrative and destructive pattern with an extensive necrotic and hemorrhagic background. Conclusion: Choriocarcinoma is a rare but highly aggressive tumor. It usually presents with symptoms resulting from metastasis to the lungs, central nervous system, or alimentary tract. In our case, considering the significant clinical history, high levels of beta-HCG, and histopathological findings, it was diagnosed as a case of choriocarcinoma of the left tubo-ovarian mass.